Body exposure and vocal analysis: validation of fundamental frequency as a correlate of emotional arousal and valence - Opladen, Vanessa; Tanck, Julia A.; Baur, Julia; Hartmann, Andrea S.; Svaldi, Jennifer; Vocks, Silja (Frontiers in Psychiatry, 2023)
Introduction Vocal analysis of fundamental frequency (f0) represents a suitable index to assess emotional activation. However, although f0 has often been used as an indicator of emotional arousal and different affective states, its psychometric properties are unclear. Specifically, there is uncertainty regarding the validity of the indices of f0mean and f0variabilitymeasures (f0dispersion, f0range, and f0SD) and whether higher or lower f0 indices are associated with higher arousal in stressful situations. The present study therefore aimed to validate f0 as a marker of vocally encoded emotional arousal, valence, and body-related distress during body exposure as a psychological stressor. Methods N = 73 female participants first underwent a 3-min, non-activating neutral reference condition, followed by a 7-min activating body exposure condition. Participants completed questionnaires on affect (i.e., arousal, valence, body-related distress), and their voice data and heart rate (HR) were recorded continuously. Vocal analyses were performed using Praat, a program for extracting paralinguistic measures from spoken audio. Results The results revealed no effects for f0 and state body dissatisfaction or general affect. F0mean correlated positively with self-reported arousal and negatively with valence, but was not correlated with HRmean/maximum. No correlations with any measure were found for any f0variabililtymeasures. Discussion Given the promising findings regarding f0mean for arousal and valence and the inconclusive findings regarding f0 as a marker of general affect and body-related distress, it may be assumed that f0mean represents a valid global marker of emotional arousal and valence rather than of concrete body-related distress. In view of the present findings regarding the validity of f0, it may be suggested that f0mean, but not f0variabilitymeasures, can be used to assess emotional arousal and valence in addition to self-report measures, which is less intrusive than conventional psychophysiological measures.